Rare MSI-H hepatoid adenocarcinoma of the colon with BRAF V600E mutation achieving long-term disease-free survival after adjuvant envafolimab: a case report - Fan, Shaoqing; Meng, Qingyu; Zhao, Zeming; Niu, Wenbo (Frontiers in Immunology, 2025)
Case presentationMicrosatellite instability-high (MSI-H) or mismatch repair-deficient (dMMR) colorectal cancer (CRC) is characterized by high tumor mutational burden and strong immunogenicity, making it responsive to immune checkpoint inhibitors. Hepatoid adenocarcinoma (HAC) of the colon is an exceptionally rare and aggressive subtype, often resistant to conventional chemotherapy. We report a 77-year-old woman who presented with progressive anemia and a right-sided colonic mass. She underwent laparoscopic radical right hemicolectomy, and pathology revealed hepatoid features with vascular and neural invasion. Immunohistochemistry showed loss of MLH1, PMS2, and MSH6, confirming dMMR status, and MSI testing indicated MSI-H. BRAF V600E mutation was identified, and germline testing excluded Lynch syndrome. Given her age and potential chemotherapy toxicity, she received eight cycles of adjuvant envafolimab (200 mg every 3 weeks). Over 38 months of follow-up, she remained disease-free without experiencing any grade ≥2 immune-related adverse events.ConclusionThis case illustrates that adjuvant PD-1 blockade can be effective and well-tolerated in elderly patients with rare MSI-H CRC subtypes, including BRAF-mutated HAC. Comprehensive molecular profiling can help guide personalized immunotherapy decisions. Further studies are needed to confirm long-term benefits, optimize treatment duration and dosing, and identify predictive biomarkers for high-risk CRC.